Animal Models in Medicine and Biology - Tvrdá, Eva; Chandra Yenisetti, Sarat (IntechOpen, 2020)
Thanks to animal models, our knowledge of biology and medicine has increased enormously over the past decades, leading to significant breakthroughs that have had a direct impact on the prevention, management and treatment of a wide array of diseases.This book presents a comprehensive reference that reflects the latest scientific research being done in a variety of medical and biological fields utilizing animal models. Chapters on Drosophila, rat, pig, rabbit, and other animal models reflect frontier research in neurology, psychiatry, cardiology, musculoskeletal disorders, reproduction, chronic diseases, epidemiology, and pain and inflammation management. Animal Models in Medicine and Biology offers scientists, clinicians, researchers and students invaluable insights into a wide range of issues at the forefront of medical and biological progress.